Reformas legales al art. 33 de la Ley Orgánica De Contratación Pública, relacionado a la declaratoria de procedimiento desierto - Abad Rengel, Franco (2015)
Article 227 of the Constitution of the Republic of Ecuador, states that public administration is a service to the community which is governed by the principles of effectiveness, efficiency, quality, hierarchy, decentralization, decentralization, coordination, participation, planning, transparency and evaluation. Within this context, the principles of transparency and openness constitute means to protect the integrity of the proceedings of the Public Administration, ie, its application results in mechanisms to meet the values and foundations of every democracy and avoid the dreaded corruption. The Magna Carta, referring to the public sector, Article 225 states that make up a. Agencies and departments of the Executive functions, Legislative, Judicial, Electoral and Transparency and Social Control; b. The entities comprising the autonomous decentralized system; c. Bodies and agencies created by the Constitution or the law for the exercise of state authority for the provision of public services or to develop economic activities undertaken by the State; d. Legal entities created by legislative act of the autonomous governments to provide public services, 6 consequently all these institutions should follow the guidelines established by the Organic Law of the National System of Public Procurement for the purpose of concluding a contract In accordance with the Constitution of the Republic of Ecuador, Spain, is a rule of law, founded on the primacy of the general interest, whose essential purpose is to serve the community and promote general prosperity, ensuring the principles, duties and constitutional rights. To fulfill the purposes of the State, the provision of goods and services by public bodies through the procurement is necessary. Then the subject of the contracts is none other than the procurement of goods and services aimed at achieving the objectives of the State in legal, harmonica and effectively. According to what is stated in art. 33 of the Law on Public Procurement, the highest authority of the Contracting Entity, provided before deciding the award, shall declare the proceedings in whole or in part, in the following cases: a. For failure to submit an offer; b. Having been disqualified bids for breach of conditions or requirements set forth in the Contract Documents; c. Not held the contract for reasons attributable to the successful tenderer, provided it is not possible to award the contract to 7 another bidder; and d. By drawbacks considered for national or institutional or all offers submitted only interests. The declaration of inconvenience should be supported by economic, technical or legal reasons. In my opinion I think it is necessary to increase other causes for which the entity can declare the procedure, such as: a. That the procedure has substantial omissions or the requirements of the specification deviations. b.The furnishes false information; and. c) If the tenderer does not enter the contract within the time prescribed by this Act, in order to find solutions, to help improve and have an efficient, effective rule allowing fulfill in order to have the Civil Service as satisfying collective and institutional and avoid setbacks that may affect the contracting parties, in order to avoid accidents that can cause serious problems, needs, be they legal, technical or economic